Nasal turbinate lymphatic obstruction: a proposed new paradigm in the etiology of essential hypertension - Phillips, William Thomas; Schwartz, Joyce Gensberg (Frontiers in Medicine, 2024)
Hypertension affects an estimated 1.3 billion people worldwide and is considered the number one contributor to mortality via stroke, heart failure, renal failure, and dementia. Although the physiologic mechanisms leading to the development of essential hypertension are poorly understood, the regulation of cerebral perfusion has been proposed as a primary cause. This article proposes a novel etiology for essential hypertension. Our hypothesis developed from a review of nuclear medicine scans, where the authors observed a significantly abnormal increase in nasal turbinate vasodilation in hypertensive patients using quantitative region of interest analysis. The authors propose that nasal turbinate vasodilation and resultant blood pooling obstruct the flow of cerebrospinal fluid passing through nasal turbinate lymphatics, thereby increasing intracranial pressure. The authors discuss the glymphatic/lymphatic clearance system which is impaired with age, and at which time hypertension also develops. The increased intracranial pressure leads to compensatory hypertension via Cushing’s mechanism, i.e., the selfish brain hypothesis. The nasal turbinate vasodilation, due to increased parasympathetic activity, occurs simultaneously along with the well-established increased sympathetic activity of the cardiovascular system. The increased parasympathetic activity is likely due to an autonomic imbalance secondary to the increase in worldwide consumption of processed food. This hypothesis explains the rapid worldwide rise in essential hypertension in the last 50 years and offers a novel mechanism and a new paradigm for the etiology of essential hypertension. This new paradigm offers compelling evidence for the modulation of parasympathetic nervous system activity as a novel treatment strategy, specifically targeting nasal turbinate regulation, to treat diseases such as hypertension, idiopathic intracranial hypertension, and degenerative brain diseases. The proposed mechanism of essential hypertension presented in this paper is a working hypothesis and confirmatory studies will be needed.